2008
DOI: 10.1590/s0100-67622008000100005
|View full text |Cite
|
Sign up to set email alerts
|

Estresses hídrico e salino no processo germinativo das sementes de Plantago ovata Forsk. (Plantaginaceae)

Abstract: 33RESUMO -Plantago ovata é espécie medicinal de grande importância cultivada na Índia, no Irã e no Paquistão. As sementes possuem de 20 a 30% de mucilagem utilizada pelas indústrias farmacêuticas nos tratamentos de constipação crônica, câncer intestinal e amebíase. A Índia é o principal exportador mundial das sementes de Plantago ovata, tendo o produto comercial com essas sementes, no Brasil, o nome de Agiolax. O objetivo deste trabalho foi avaliar os possíveis efeitos dos estresses hídrico e salino na germina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
0
4
0
2
Order By: Relevance
“…Moraes, Menezes and Pasqualli (2005) evaluated osmotic potentials on common bean (Phaseolus vulgaris L.) seeds and found reduced germination (p<0.05) from -0.2 MPa, with no normal seedling formation from -0.25 MPa. Souza et al (2008) evaluated water stress induced by PEG-6000 in Plantago ovata seeds and found reduced germination and GSI from -0.2 MPa, which were totally inhibited at osmotic potentials of -0.6 and -0.8 MPa. The use of mannitol showed a linear decrease in germination and GSI as a function of the osmotic potentials evaluated (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Moraes, Menezes and Pasqualli (2005) evaluated osmotic potentials on common bean (Phaseolus vulgaris L.) seeds and found reduced germination (p<0.05) from -0.2 MPa, with no normal seedling formation from -0.25 MPa. Souza et al (2008) evaluated water stress induced by PEG-6000 in Plantago ovata seeds and found reduced germination and GSI from -0.2 MPa, which were totally inhibited at osmotic potentials of -0.6 and -0.8 MPa. The use of mannitol showed a linear decrease in germination and GSI as a function of the osmotic potentials evaluated (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Lavezo et al (2015) worked with seeds of Petiveria alliacea L. and negative osmotic potentials of -0.4 and -0.5 MPa and found there was no germination when using CaCl 2 and NaCl agents, respectively. In addition, Sousa et al (2008) observed that the germination percentage of Plantago ovata seeds significantly decreased with potentials starting at -0.4 MPa of NaCl and CaCl 2 , and Rosa et al (2015) analyzed seeds of Salvia splendens and observed elevated indices of seed death and abnormal seedlings in the presence of NaCl and KCl. On the other hand, some studied have demonstrated that chia seeds tolerate certain levels of salinity, such as Dal' Maso et al (2013) (KCl).…”
Section: Degrees Of Freedommentioning
confidence: 99%
“…This inhibits the germination potential of cultures, as found in the following studies: Plantago ovata Forssk. (Sousa et al, 2008); Salvia aegyptiaca L. (Gorai et al, 2011); Prosopis juliflora (Sw.) DC. (Nasr et al, 2011); Ochroma pyramidale (Cav.…”
Section: Introductionmentioning
confidence: 99%
“…(Moura et al, 2011), in Plantago ovata Forsk. at potentials below -0.2 MPa (Sousa et al, 2008) and for Foeniculum vulgare Miller at osmotic potential of -0.1 MPa (Stefanello et al, 2006). These results indicate that each species has a maximum level of osmotic potential at which GSI is not affected.…”
Section: Sources Of Variation F Values Temperatures (T) Potentials (P)mentioning
confidence: 69%